Design optimization and motion control strategy discussion in self - designed tribometer - Guo, Shu En (2015)
A self-designed tribometer designed by a previous batch of FYP students was developed to study the generation of frictional hysteresis under different loadings and displacement functions to replicate different scenarios. However, the system could be further improved because of the presence of stiction phenomenon in the motion control of DC motor. Firstly, with the previous design, unstable alignment would occur and the test sample will glide out due to the position of the test sample being placed on the moving block. Improvements were made on the design of the friction block to ensure that the full surface area of the material is in contact with the moving block for higher stability by mounting it onto the friction block. In addition, with this improved friction block design, it could ensure that the test results obtained are much more accurate because we are obtaining the results on the full surface of the test sample and most importantly, we could assess the material effect on the friction much more easily. Secondly, three optimization designs, pizeotechnology, a clamp-spring and a slider-bolt-spring solution, were developed to improve motion control in order to minimize the stiction during velocity reversal. By comparing these three designs, a slider-bolt-spring was selected to be implemented in the self-designed tribometer system. However, after conducting the experiment, it was found out that there was little significant improvement of the stiction despite applying a slider-bolt-spring into the self-designed tribometer system. As such, control strategy is being considered instead. Thirdly, in order to study the control strategy of PID-feedback, PID-feedforward, PID-feedback-feedforward and PID-cascade control, tuning is required before we could start the experiment. Finally, with the achievement mentioned above, a better friction measurement and motion control was obtained.